Pengembangan E-Modul Membaca Siswa Kelas 3 SDN 029 Pekanbaru - Isra Syahputri; Febrina Dafit (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This development research was carried out based on the teacher's difficulty in presenting complete and interesting teaching materials so that students were less enthusiastic when the learning process took place. This study aims to test the feasibility of teaching materials in the form of e-modules on theme 2 sub-theme 3 for third grade elementary school. This research is a development research using the ADDIE model. The stages of the ADDIE model to develop this e-module were modified into three stages, namely analysis, design and development. The data collected in this study are quantitative data and qualitative data. The methods used to collect data are: observation, interviews, and questionnaires. The subjects involved in this study were 2 design experts, 2 material experts and 2 linguists. The data analysis technique used is quantitative and qualitative descriptive data analysis techniques. The results showed that the validation of design experts obtained an average of 92.31% in the